2021
DOI: 10.3390/magnetochemistry7090121
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of Benchtop Nuclear Magnetic Resonance Spectroscopy

Abstract: Benchtop nuclear magnetic resonance (NMR) spectroscopy uses small permanent magnets to generate magnetic fields and therefore offers the advantages of operational simplicity and reasonable cost, presenting a viable alternative to high-field NMR spectroscopy. In particular, the use of benchtop NMR spectroscopy for rapid in-field analysis, e.g., for quality control or forensic science purposes, has attracted considerable attention. As benchtop NMR spectrometers are sufficiently compact to be operated in a fume h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 124 publications
0
15
0
Order By: Relevance
“…We decided to synthesize the trifluorinated counterparts of monastrol and LaSOM-63 because of the bioorthogonal nature of fluorine and the increased metabolic stability offered by the presence of carbon–fluorine bonds. Of note, while it has been reported that the substitution of a β-ketoester with a 4,4,4-trifluorinated ketoester can be used to prepare trifluorinated versions of these dihydropyrimidinones and tetrahydropyrimidinones through the Biginelli reaction, the operative mechanism through which the Biginelli proceeds with 4,4,4-trifluoroketoesters has not been investigated. Recent advances in benchtop nuclear magnetic resonance (NMR) spectroscopy have allowed for noncanonical applications of NMR spectroscopy as an analytical tool directly in a synthetic laboratory setting, including real-time reaction monitoring. …”
Section: Introductionmentioning
confidence: 99%
“…We decided to synthesize the trifluorinated counterparts of monastrol and LaSOM-63 because of the bioorthogonal nature of fluorine and the increased metabolic stability offered by the presence of carbon–fluorine bonds. Of note, while it has been reported that the substitution of a β-ketoester with a 4,4,4-trifluorinated ketoester can be used to prepare trifluorinated versions of these dihydropyrimidinones and tetrahydropyrimidinones through the Biginelli reaction, the operative mechanism through which the Biginelli proceeds with 4,4,4-trifluoroketoesters has not been investigated. Recent advances in benchtop nuclear magnetic resonance (NMR) spectroscopy have allowed for noncanonical applications of NMR spectroscopy as an analytical tool directly in a synthetic laboratory setting, including real-time reaction monitoring. …”
Section: Introductionmentioning
confidence: 99%
“…Benchtop NMR spectrometers typically utilize permanent magnets that generate a static magnetic field of up to 2 T, corresponding to a proton resonance frequency of 80 MHz [33] . Permanent magnets do not require cryogenic cooling, reducing the technical maintenance and maintenance cost [34] . Typically, benchtop NMR spectrometer prices range from £30,000 to £150,000 providing a less expensive alternative to high‐field spectrometers.…”
Section: Introductionmentioning
confidence: 99%
“…[33] Permanent magnets do not require cryogenic cooling, reducing the technical maintenance and maintenance cost. [34] Typically, benchtop NMR spectrometer prices range from £30,000 to £150,000 providing a less expensive alternative to high-field spectrometers. Most benchtop NMR spectrometers have an external locking system and hence protiated solvents can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in benchtop nuclear magnetic resonance (NMR) spectroscopy have allowed for non-canonical applications of NMR spectroscopy as an analytical tool directly in a synthetic laboratory setting, including real time reaction monitoring. [20][21][22][23] Here, we utilize benchtop 19 F NMR spectroscopy to probe the mechanism of the Biginelli cyclocondensation of trifluorinated ketoesters by tracking the production of various aryl substituted trifluorinated tetrahydropyrimidinones and their reactive intermediates in real time. In this study, a library of various 3-and 4-substituted aromatic aldehydes not only gave access to a diverse library of 6-aryl trifluorinated tetrahydroprymidines, but also provided mechanistic insight into the Biginelli through meta-and para-Hammett linear free energy relationships (LFER) derived from 19 F NMR spectra of crude reaction mixtures [24,25].…”
Section: Introductionmentioning
confidence: 99%